Molecular Organization of Phospholipid Monolayers on the Water Surface by Maxwell Displacement Current Measurement - Sulaiman, Khaulah; Abd Majid, Wan Haliza; Muhamad, Muhamad Rasat (Elsevier, 2006)
The monolayer of organic molecules at the air-water interface has been studied using the Maxwell displacement current (MDC) technique. The materials used in this study were the biological materials of phosphatidyl ethanolamine (PE) and phosphatidic acids (PA). The configuration of the experimental set-up consists of the metal/air-gap/monolayer/metal coupled with the Langmuir method. This measurement enables the detection of current without destroying the monolayer. The phase transition and molecular orientation of the phospholipid monolayers were investigated using MDC measurement without mechanical contact between electrodes and the materials. Direct evidence of phase transition from gaseous to the polar ordering phase can be obtained across phospholipid monolayers even though at very low surface pressure. Relaxation process of the phospholipid monolayers was investigated by using the step compression on the MDC signals. (c) 2005 Elsevier B.V. All rights reserved.